Sosial Ekonomi Nelayan Pesisir Pantai Desa Swarangan Kecamatan Jorong Kabupaten Tanah Laut - Ika Chandriyanti; Eny Fahrati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2020)
Abstract- The economic activities of the people on the coast are identical to fishers. Most economic activities are fishing for a lot of fish and processed products (post-harvest marine products). Natural conditions are a factor in the high risk of anglers at sea and are always in economic uncertainty, impacting fishers' income level. This study aims to determine the fishermen community's socio-economic characteristics in Swarangan village, the average income, and to compare the average income per capita with the poverty line. The research method used in this research is a descriptive quantitative method with as many as 62 fishermen samples. The results showed that 1) fishermen's characteristics are still of productive age, have an average junior high school education, and have a side job. 2). The average income from fishing (as fishermen) is mostly below the poverty line. 3) the average total pay of a small proportion of families is below the poverty line. In general, the socio-economic conditions of fishers in Swarangan village are still above the poverty line. Keywords: fishermen, income, poverty line